2020
DOI: 10.1186/s42523-020-00041-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome–host co-oscillation patterns in remodeling of colonic homeostasis during adaptation to a high-grain diet in a sheep model

Abstract: Background Ruminant gastrointestinal tract homeostasis deploys interactive microbiome–host metabolic communication and signaling axes to underpin the fitness of the host. After this stable niche is destroyed by environmental triggers, remodeling of homeostasis can occur as a spontaneous physiological compensatory actor. Results In this study, 20 sheep were randomly divided into four groups: a hay-fed control (CON) group and a high-grain (HG) diet group for 7, 14, or 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
1
6
1
Order By: Relevance
“…However, studies on the mucosal microbiota of the ileum and the effects of HG or HP diets on them are limited. At present, 16S rRNA sequencing with an Illumina MiSeq Platform provides an efficient mean to study the intestinal microbiota ( Rapin et al, 2017 ), and also has been widely used in ruminant researches ( Li et al, 2018 ; Lin et al, 2020 ). Through sequencing, our results provide an overview of the microbial composition of the ileal mucosa of the Hu sheep.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies on the mucosal microbiota of the ileum and the effects of HG or HP diets on them are limited. At present, 16S rRNA sequencing with an Illumina MiSeq Platform provides an efficient mean to study the intestinal microbiota ( Rapin et al, 2017 ), and also has been widely used in ruminant researches ( Li et al, 2018 ; Lin et al, 2020 ). Through sequencing, our results provide an overview of the microbial composition of the ileal mucosa of the Hu sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The diet fed to ruminants is the primary determinant of bacterial community structure (95)(96)(97). Co-oscillations of microbiota are very important to maintaining homeostasis in gastrointestinal ecology after dietary perturbations (98). It is important to adjust the animal diet according to their age and physiological condition and to provide proper time to adapt to different dietary changes.…”
Section: Diet-microbe Interactionsmentioning
confidence: 99%
“…Feeding a high-starch diet can directly affect the colonic lumen environment, which in turn alters the lumen-specific functional taxonomic groups ( Akkermansia , unclassified Christensenellaceae , and vadinBB60 ). Consequently, the colonic epithelium makes a new niche that triggers cell apoptosis to achieve a functional transformation ( 98 ). These studies suggested that microbe–host interaction is vital for remodeling of hindgut homeostasis to allow adaptation to dietary perturbations.…”
Section: Diet–microbe Interactionsmentioning
confidence: 99%
“…A 1% agarose gel electrophoresis was used to assess the quality of the extracted DNA. The primers 338F (5 0 -ACTCCTACGG-GAGGCAG CAG-3 0 ) and 806R (5 0 -GGACTACHVGGGTWTCTAAT-3 0 )on a thermocycler PCR system (Gene Amp 9700, ABI, USA) were used to amplify the V3eV4 region of the DNA (Lin et al, 2020). The pairedend sequencing (2 Â 300 bp) on an Illumina MiSeq platform (Illumina, San Diego, USA) was conducted according to the standard Major Biobio-Pharm Technology Co. Ltd. (Shanghai, China) protocols on the pooled equimolar ratios of the purified amplicons.…”
Section: S Rrna Gene Profilingmentioning
confidence: 99%